Pengaruh Inisiasi Menyusui Dini (IMD) Terhadap Hipotermi Pada Bayi Baru Lahir Peningkatan Produksi ASI Pada Ibu Post Partum - Putri Winasari; Utari Christya Wardhani; Sri Muharni (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Infant deaths generally occur in the early neonatal period due to hypothermia. The incidence of hypothermia in newborns is quite high, globally ranging from 8.5-52%, an estimated 17 million newborns experience hypothermia in developing countries. The incidence of hypothermia in newborn babies is 92.3%, the infant mortality rate due to hypothermia is 6.3%. One intervention to minimize the incidence of hypothermia in newborn babies is to initiate early breastfeeding. The aim of the research was to determine the effect of early initiation of breastfeeding on hypothermia in newborn babies at the Bakti Timah Karimun Hospital. The research method used a pre-experiment with a one group pretest-posttest design. The sampling technique was purposive sampling with 14 respondents. The measuring instruments in this study were a digital axillary thermometer, standard operating procedures (SOP) for early breastfeeding initiation and observation sheets. Data analysis using paired sample t-test. The results of the paired sample t-test found a p-value = 0.000 (p<0.05), so it can be concluded that there is an influence of early initiation of breastfeeding on hypothermia in newborn babies in the Midwifery Room at Bakti Timah Karimun Hospital. Early initiation of breastfeeding can be used as an intervention for newborns to minimize the incidence of hypothermia